Self-Charging Drone - Marafie, Ahmed (2019)
Drones are a very useful piece of technology. They have many functionalities and they are used in different fields. For example, surveillance, medical assistance or even as a hobby. However, a major limitation to drones is their battery life. The average battery life of a drone is 20 minutes. With this battery life, a surveillance drone for example, can only cover a certain area before needing to go back to the owner for a battery change or to charge. Our solution is to create charging stations, where drones can self-charge whenever it is required and then continue with their task. These charging stations will be placed high enough so that the drones are un-interrupted, and they will always be charging the batteries, so they are available whenever needed.